Antioksidan Dari Daun Sirih Merah (Piper Crocatum) - Jeane Maria Mustika Tonahi; Siti Nuryanti; Suherman Suherman (Jurnal Akademika Kimia, 2014)
Research on the antioxidant activity testing has been done using red betel (Piper crocatum) leafs in Palu, Central Sulawesi. This research was conducted to determine the IC50 value and antioxidant activity of red betel leafs extracts which has the ability as a natural antioxidant. This research was conducted with an experimental method using an extraction maceration technique, DPPH (1,1-diphenyl-2-pikrilhidrazil) as free radicals, vitamin C as a positive control, UV-Vis spectrophotometer as an antioxidant test equipment with red betel leafs extracts as samples. Samples of red betel leaves were used as much as 30 grams, and the solvent were absolute ethanol. Various concentrations of the red betel leafs extracts were 20 ppm, 40 ppm, 60 ppm, and 80 ppm. Testing of antioxidant activity was done by using a UV-Vis Spectrophotometer and IC50. The results showed that the IC50 value of the red betel leafs (Piper crocatum) extracts was 47.45 ppm. The red betel leafs extract was categorized into a very powerful antioxidant based on IC50 value, where the optimum percentage of red betel leaf extract activity in inhibiting free radical was 81.82%.